Speculative Possibilities: Indigenous Futurity, Horror Fiction, and The Only Good Indians - Rikard, Nicole R. (Transmotion, 2023)
An exciting movement in literature (as well as art, music, gaming, and other forms of media) that is presently exploding throughout our media streams in the twenty-first century is that of Indigenous futurism. This concept, which owes its namesake to scholar Grace L. Dillon and her work Walking the Clouds: An Anthology of Indigenous Science Fiction (2012), seeks to explore the possibilities of alternate pasts, presents, and futures, offering a fresh perspective on the beauty, power, and resilience of Indigeneity. One writer delving into this movement is Stephen Graham Jones, prolific author of many novels and short stories including his most recent works The Babysitter Lives (2022), The Backbone of the World (2022), “Attack of the 50 Foot Indian” (2021), “How to Break into a Hotel Room” (2021), My Heart is a Chainsaw (2021), “Wait for the Night” (2020), Night of the Mannequins (2020), and “The Guy with the Name” (2020), and The Only Good Indians (2020). Although Jones’s contributions to the literary world are extensive, there has been relatively little scholarship dedicated to his continuous experimenting in varying genres, forms, and subject matters. Likewise, scholarship on Indigenous futurism is also quite scarce, especially as it is developed through the literary genre of horror fiction. This work extends both scholarly conversations by analyzing Jones’s The Only Good Indians as a work of Indigenous futurism, specifically as it relates to rewriting the past, present, and future through various methods of Native slipstream. Fictional newspaper headlines and articles, a concentrated insistence on rationalization coupled with the inability to achieve such measures, and varying points of view combine to create a novel that is a hauntingly beautiful depiction of resiliency and possibility for an alternative future in which Indigenous worldviews replace the damaging cycles created and perpetuated by Western ideologies—positioning The Only Good Indians as an exceptional contribution to the field of Indigenous futurism, in addition to substantiating that both horror and futuristic fiction can serve as an effective medium of decolonization. Keywords: Indigenous futurism, decolonization, horror, Stephen Graham Jones, speculative fiction